EFFECT OF BREAST CONSERVING SURGERY IN QUALITY OF LIFE IN BREAST CANCER PATIENTS - Yasemin Zanapalıoğlu; Kemal Atahan; Serhat Gür; Atilla Çökmez; Ercüment Tarcan (European Journal of Breast Health, 2009)

(untitled)
Purpose:Breast cancer is the most common cancer among women and the second leading cause of the cancer deaths. To assess the eff ect of adjuvant treatment modalities on the quality of life scales between the two groups of patients who underwent breast conserving surgery (BCS) or modifi ed radical mastectomy (MRM).Patients and Methods:74 breast cancer patients whose follow-up exceeds minimum 12 months from diagnosis without any recurrence and distant metastasis and who accepted to take the questionnaire was admitted to the study group. These patients were given a questionnaire consisting of 53 questions about functional status, well-being sense and symptoms. That was a Turkish-translated version of European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 Quality of life scale version 3-Turkish and EORTC QLQ-BR23 for assessment of quality of life.Results:Quality of life after BCS was found better than MRM for well-being sense, physical status, role performance, emotional status, cognitive status, social status, fatigue, nausea-vomiting, pain respiratory distress, sleep disorders, anorexia, constipation, diarrhea, fi nancial problems, body image, sexual functions, sexual satisfaction, future anxiety, arm symptoms and breast symptoms.Conclusion: Our results suggest that breast conserving surgery will positively aff ect not only the patient but also the people who were living with her.